Preventive role of social interaction for cocaine conditioned place preference: correlation with FosB/DeltaFosB and pCREB expression in rat mesocorticolimbic areas - El Rawas, Rana; Klement, Sabine; Salti, Ahmad; Fritz, Michael; Dechant, Georg; Saria, Alois; Zernig, Gerald (Frontiers in Behavioral Neuroscience, 2012)
The worsening of drug abuse by drug-associated social interaction is a well-studied phenomenon. In contrast, the molecular mechanisms of the beneficial effect of social interaction, if offered as a mutually exclusive choice to drugs of abuse, are under-investigated. In a rat place preference conditioning (CPP) paradigm, four 15 min episodes of social interaction with a gender- and weight matched male early-adult conspecific inhibited cocaine-induced reinstatement of cocaine CPP, a model of relapse. These protective effects of social interaction were paralleled by a reduced activation, as assessed by Zif268 expression in brain areas known to play pivotal roles in drug-seeking behavior. Here we show that social interaction during extinction of cocaine CPP also reduced cocaine-CPP-stimulated FosB expression in the nucleus accumbens shell and core. In addition, social interaction during cocaine CPP extinction increased pCREB (cAMP response element binding protein) expression in the nucleus accumbens shell and the cingulate cortex area 1 (Cg1). Our results show that FosB and pCREB may be implicated in the protective effect of social interaction against cocaine-induced reinstatement of CPP. Thus, social interaction, if offered in a context that is clearly distinct from the previously drug-associated one, may profoundly inhibit relapse to cocaine addiction.